2014
DOI: 10.1186/1471-2474-15-449
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of antiviral prophylaxis correlates with high prevalence of hepatitis B virus (HBV) reactivation in rheumatoid arthritis patients with HBV carrier state: a real-world clinical practice

Abstract: BackgroundTo investigate the risk of hepatitis B virus (HBV) reactivation in rheumatoid arthritis (RA) patients with HBV carrier state during treatment of disease-modifying antirheumatic drugs (DMARDs) and the use of antiviral prophylaxis in real-world clinical practice.MethodsConsecutive RA patients with HBV carrier state were included. Clinical data including liver evaluation, HBV infection evaluation and the use of antiviral prophylaxis were recorded.ResultsFifty-three RA patients with HBV carrier state wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…The characteristics of the included studies are shown in Table . The study design for most of the included studies was retrospective or prospective observational (n = 23), and 21 were conducted in a single‐center setting.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Table . The study design for most of the included studies was retrospective or prospective observational (n = 23), and 21 were conducted in a single‐center setting.…”
Section: Resultsmentioning
confidence: 99%
“…5 Patients with autoimmune diseases such as rheumatoid arthritis (RA) receiving immunosuppressive treatment are also considered to be a risk group. Nevertheless, to date, only case reports 6,7 or cohort studies with small sample sizes [8][9][10][11][12][13][14] have been conducted to investigate the risk of HBV reactivation in patients with RA receiving immunosuppressive therapy. Furthermore, no studies have been conducted to investigate the incidence of fulminant hepatitis due to HBV reactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a study in China on HB carriers with RA, HB reactivations or patients developing hepatitis after reactivation were less frequent in the present study. 3 Established antiviral effectiveness of entecavir was confirmed here, but the above definition of HB reactivation might not be unequivocal because serum HBV-DNA levels often fluctuate. Additionally, whether csDMARDs having almost no immunosuppressive activity can be a risk for HB reactivation still needs to be elucidated.…”
Section: Dear Editormentioning
confidence: 69%
“…1,2 Reactivation of HB occurs in 8-36% of HB carriers with RA, especially in those not receiving prophylactic treatment with antiviral nucleos(t)ide analogues (NAs). 2,3 However, factors determining the risk of reactivation are not well established, and the effectiveness of NAs remains uncertain. Hence, to determine the incidence and risk of HB reactivation, we prospectively investigated HB carriers with RA in 14 hospitals throughout Japan from 2012 to 2017.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation